The green paradox and learning-by-doing in the renewable energy sector - Nachtigall, Daniel; Rübbelke, Dirk T. G. 1972- (Freie Univ. Berlin, FB Wirtschaftswiss., 2014)
The green paradox conveys the idea that climate policies may have unintended side effects when taking into account the reaction of fossil fuel suppliers. In particular, carbon taxes that will be implemented in the future induce resource owners to extract more rapidly which increases present carbon dioxide emissions and accelerates global warming. Our results suggest that future carbon taxes may even decrease present emissions if resource owners face increasing marginal extraction costs and if there is a clean energy source that is a perfect substitute and exhibits learning-by-doing (LBD). If the marginal extraction cost curve is sufficiently at, resource owners respond to a future carbon tax with lowering total extraction and only slightly increase present extraction. Moreover, taxation leads to higher energy prices which induces the renewable energy firms to increase output not only in the future, but also in the present because of the anticipated benefits from LBD. This crowds out energy from the combustion of fossil fuels and may outweigh the initial increase in present extraction, leading to less emissions in the present.
Keywords: Widerspruch; Energiewirtschaft; Erneuerbare Energien; Anthropogene Klimaänderung